A new design of embedded monitoring system for maintenance and performance monitoring of a cane harvester tractor - Estiko Rijanto; Erik Adiwiguna; Aryo Putro Sadono; Muhammad Hafil Nugraha; Oka Mahendra; Rendra Dwi Firmansyah (National Research and Innovation Agency, 2020)
In modern sugarcane farms, sugarcane chopper harvesters are becoming widely used. A modern sugarcane chopper harvester is essentially a mechatronic system composed of a tractor and some implements with several electro-hydraulic control systems. Those control systems are controlled by electronic controller units (ECUs). It may fail during harvesting operation due to lack of maintenance, operator's awareness, skill, and field contour. This paper presents a new design of an embedded monitoring system for maintenance and production performance monitoring of a sugarcane chopper harvester in a real-time manner. A prototype of the embedded monitoring system was developed which partially realized the designed system. The experimental result showed that the main computer could communicate with other ECUs using a controller area network (CAN) bus. The dataset from four channels retrieved from the CAN bus represents the real values originating from the temperature sensor simulators. Apart from being sent to the CAN bus, the data are also recorded on a secure digital (SD) Card and sent to the internet of things (IoT) server. In the update time interval testing, the 100 ms interval does not give any error.